A LOW COST PORTABLE REFRESHABLE PAPERLESS BRAILLE FOR BLIND PEOPLE - Ashwini S. Bagane; Prof. S.R. Jagtap (International Journal of Innovations in Engineering Research and Technology, 2021)
Visually impaired people are the indispensable unit of our community. Their disabilities about the eyesight make them less accessible to computer, educational software and digital data which turn to limit their own knowledge. The main problem faced by them is to read digital data in terms of Braille language. Braille language is represented by 6 dots arranged in 3x2 matrixand it is readable only through the sense of touch. This paper introduces electronic Braille which consistsof Braille reader and Braille writer. Reading is possible through tactile pin module arranged in 3x2 matrixand writing is possible through the Braille keypad. Whatever data is to be read or write will be stored in the SD card. This small electronic Braille devicewill be portable and has a low costthan that of learningmaterialsof blind people.